Assessment of the relationship between the engagement in leisure time and academic motivation among the students of faculty of education - Erdi Kaya; İhsan Sarı; Mahmut Gulle; Mehmet Cetın; Recep Kahramanoğlu (Selcuk University, 2014)
The aim of the study was to determine the relationship between leisure time motivation and academic motivation among the students who studied at the Faculty of Education of Mustafa Kemal University. 260 students (Xyears: 21.29±2.11) constituted the sample of the study. For the analyses of the data; Leisure Motivation Scale and Academic Motivation Scale were employed. The data were analyzed using descriptive statistics, Pearson's correlation test and regression analysis. According to the findings of the study; it was explored that academic motivation was significantly correlated with the leisure motivation scale's subscales of intrinsic motivation toward knowledge and accomplishment (r=0.360), experience stimulation (r=0.219) and introjected and identified regulations (r=0.212; p lt;0.05). Also; the leisure motivation scale's subscales of motivation toward knowledge and accomplishment accounted for 13% of academic motivation. In light of these findings; it may be concluded that there was a correlation between academic motivation and intrinsic motivation (toward knowledge and accomplishment, and experience stimulation) and more autonomous types of extrinsic motivation (introjected and identified regulations). As a result of the regression analysis; engagement in leisure time activities for knowledge and accomplishment significantly accounted for academic motivation. In sum; it may be interpreted that participation in leisure time activities with more intrinsic reasons may yield more positive results.